Effects of Cold Atmospheric Plasma (CAP) on ß-Defensins, Inflammatory Cytokines, and Apoptosis-Related Molecules in Keratinocytes In Vitro and In Vivo - Arndt, Stephanie (Public Library of Science, 2015)

(untitled) (PLoS One)
Cold atmospheric plasma (CAP) has been gaining increasing interest as a new approach for the treatment of skin diseases or wounds. Although this approach has demonstrated promising antibacterial activity, its exact mechanism of action remains unclear. This study explored in vitro and in vivo whether CAP influences gene expression and molecular mechanisms in keratinocytes. Our results revealed that a 2 min CAP treatment using the MicroPlaSter ß in analogy to the performed clinical studies for wound treatment induces expression of IL-8, TGF-ß1, and TGF-ß2. In vitro and in vivo assays indicated that keratinocyte proliferation, migration, and apoptotic mechanisms were not affected by the CAP treatment under the applied conditions. Further, we observed that antimicrobial peptides of the ß-defensin family are upregulated after CAP treatment. In summary, our results suggest that a 2 min application of CAP induces gene expression of key regulators important for inflammation and wound healing without causing proliferation, migration or cell death in keratinocytes. The induction of ß-defensins in keratinocytes describes an absolutely new plasma strategy. Activation of antimicrobial peptides supports the well-known antibacterial effect of CAP treatment, whereas the mechanism of ß-defensin activation by CAP is not investigated so far.